1997
DOI: 10.1046/j.1365-2141.1997.4653269.x
|View full text |Cite
|
Sign up to set email alerts
|

Tropism of human herpesvirus 8 for peripheral blood lymphocytes in patients with Castleman's disease

Abstract: Summary. Multicentric Castleman's disease (MCD), also called multicentric angiofollicular lymphoid hyperplasia, is a systemic lymphoproliferative disorder causing fever, lymphadenopathy and splenomegaly. Recently, Kaposi's sarcoma-associated herpesvirus/human herpesvirus 8 (KSHV/HHV-8) DNA sequences have been detected in cases of MCD. We examined HHV-8 DNA sequences in the peripheral blood mononuclear cells (PBMCs) of two HIVnegative patients with MCD and in PBMCs and the lymph node of a HIV-negative patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…We first tested NF-AT activation by vGPCR in Tlymphoid (Jurkat) cells because T cells express high levels of NF-AT protein, making it easy to measure NF-AT activation. T cells of patients with HHV-8-related diseases are infected, although not abundantly (41,42,45; M. C. Sirianni, L. Vincenzi, S. Topino, E. Scala, A. Angeloni, R. Gonnella, S. Uccini, and A. Faggioni, Letter, J. Infect. Dis.…”
Section: Results Vgpcr Activates Nf-atmentioning
confidence: 99%
“…We first tested NF-AT activation by vGPCR in Tlymphoid (Jurkat) cells because T cells express high levels of NF-AT protein, making it easy to measure NF-AT activation. T cells of patients with HHV-8-related diseases are infected, although not abundantly (41,42,45; M. C. Sirianni, L. Vincenzi, S. Topino, E. Scala, A. Angeloni, R. Gonnella, S. Uccini, and A. Faggioni, Letter, J. Infect. Dis.…”
Section: Results Vgpcr Activates Nf-atmentioning
confidence: 99%
“…Like other gammaherpesviruses, KSHV is lymphotropic (1,5,6,20,30,35,98) and replicates both latently and lytically (59,70,71,105). Following primary infection, KSHV establishes latency in CD19 ϩ B cells (and possibly other cells types) (7).…”
mentioning
confidence: 99%
“…Complexes were washed extensively, beads were boiled in 2ϫ Laemmli buffer, and bound proteins were displayed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). 35 S-labeled proteins were visualized by autoradiography after amplifying signals in 0.5 M salicylic acid.…”
mentioning
confidence: 99%
“…A serological study showed that over 95% of rhesus monkeys are strongly positive for the presence of antibodies to this herpesvirus, suggesting that rhesus monkeys are a natural host for RRV infection (31). While specific diseases associated with RRV remain to be determined, some of the naïve seronegative rhesus macaques inoculated with RRV developed lymphadenopathy and vascular hyperplasia (85,140) similar to that observed in KSHV-infected men (18,66,130). Furthermore, inoculated monkeys remained persistently infected with RRV (85).…”
Section: The Lymphocryptoviruses (Gamma-1) Include Epstein-barr Virusmentioning
confidence: 99%
“…MCD is an atypical lymphoproliferative disorder that includes hyperplasia, lymphadenopathy, and splenomegaly. Both HIV-infected and -uninfected individuals develop MCD, although there is a high rate of KSHV infection in the lymph nodes of HIV patients with MCD (18,66,130). It has been demonstrated that viral interleukin-6 (IL-6) acts as an autocrine or paracrine factor in the lymphoproliferative processes common to both BCBLs and MCD (111,131).…”
Section: The Lymphocryptoviruses (Gamma-1) Include Epstein-barr Virusmentioning
confidence: 99%